The Association Between Adverse Childhood Experiences and Postpartum Depression - Prentice, Danielle M.; Otaibi, Banan W.; Stetter, Christy; Kunselman, Allen R.; Ural, Serdar H. (Frontiers in Global Women's Health, 2022)
Objective Adverse childhood experiences (ACEs) are linked to worsening overall health outcomes and psychological diagnoses. Routine screening, particularly in patients with postpartum depression (PPD), would identify patients who could benefit from interventions to prevent the perpetuation of ACEs and establish a system of preventative care to mitigate the risks of adverse health outcomes associated with high ACE scores. The purpose of this study is to explore the link between ACEs and PPD to advocate for the use of the ACE questionnaire as a routine screening tool in all pregnant patients diagnosed with PPD. We hypothesize that a cohort of patients with PPD will be more likely to have high-risk ACE scores than the general female population. Study Design Our IRB approved, retrospective cohort study identified all patients diagnosed with PPD at an academic medical center between January 2015 and December 2019. The subjects were identified using retrospective chart review. Subjects were recruited via telephone and asked to complete an ACE questionnaire. Questionnaires were sent via RedCap. ACE scores were calculated, categorized as 0, 1, 2, 3, or 4 or more ACEs, and compared to the prevalence in the original Kaiser-CDC ACE study female cohort using a chi-square goodness-of-fit test. Results There were 132/251 surveys completed (53% response rate). In our PPD population, 19.3% had 0 ACEs, 17.0% had 1 ACE, 13.1% had 2 ACEs, 16.5% had 3 ACEs, and 34.1% had 4 or more ACEs. These percentages were significantly different from the Kaiser-CDC ACE Study percentages of 34.5, 24.5, 15.5, 10.3, and 15.2%, respectively (p < 0.001). Conclusion Our unique study showed that women with PPD are more likely to have high-risk ACE scores than the general female population. This finding has important implications in regards to counseling, intervening to prevent perpetual ACEs, and establishing important provider-patient relationships for life-long preventative care. Non-gendered language is used when possible throughout. However, the wording from studies cited in this paper was preserved.